Mycophenolate mofetil in patients with anti‐neutrophil cytoplasmic antibody‐associated vasculitis: a prospective pharmacokinetics and clinical study. (May 2014) - Chaigne, B.; Gatault, P.; Darrouzain, F.; Barbet, C.; Degenne, D.; François, M.; Szymanski, P.; Rabot, N.; Golea, G.; Diot, E.; Maillot, F.; Lebranchu, Y.; et al.
Summary Anti‐neutrophil cytoplasmic antibody‐associated vasculitis (AAV) treatment strategy is based on immunosuppressive agents. Little information is available concerning mycophenolic acid (MPA) and the area under the curve (AUC) in patients treated for AAV. We evaluated the variations in pharmacokinetics for MPA in patients with AAV and the relationship between MPA–AUC and markers of the disease. MPA blood concentrations were measured through the enzyme‐multiplied immunotechnique (C0, C30, C1, C2, C3, C4, C6 and C9) to determine the AUC. Eighteen patients were included in the study. The median (range) MPA AUC0–12 was 50·55 (30·9–105·4) mg/h/l. The highest coefficient of determination between MPA AUC and single concentrations was observed with C3 (P < 0·0001) and C2 (P < 0·0001) and with C4 (P < 0·0005) or C0 (P < 0·001). Using linear regression, the best estimation of MPA AUC was provided by a model including C30, C2 and C4: AUC = 8·5 + 0·77 C30 + 4·0 C2 + 1·7 C4 (P < 0·0001). Moreover, there was a significant relationship between MPA AUC0‐12 and lymphocyte count (P < 0·01), especially CD19 (P < 0·005), CD8 (P < 0·05) and CD56 (P < 0·05). Our results confirm the interindividual variability of MPA AUC in patients treated with MMF in AAV and support a personalized therapy according to blood levels of MPA.